Measurements of Electron Energy Spectrum During High Power of Microwave Cavity; XIIIth International Symposium on Discharges and Electrical Insulation in Vacuum, Paris, Conservatoire national des arts et métiers, June 27-30, 1988; Vol. 2 - Novikov S. A. Sergey Avtonomovich; Razin S. V.; Chumerin P. Yu. Pavel Yurievich; Yushkov Y. G. Yuri Georgievich (1988, 1988)
В фонде НТБ ТПУ отсутствует